The belvedere torso’s influence as an accidental fragment in art, from the renaissance to the xixth century (2012)
The discovery of the Belvedere Torso in the early XVthcentury changed the philosophical notions about theconception of the work of art. The Torso was consideredan incomplete piece, albeit perfect, and helped to madeawareness about the ideas of a finished, a fragmentaryor a ruined work of art. From the Renaissance to theXIXth century, artists found themselves inspired by theTorso, not just by its formal aspects, but also because itactivated imagination and because of the power conferredto the observer as an active participant in the receptionof the work of art.